Additional MRI for initial M-staging in pancreatic cancer: a cost-effectiveness analysis - Gassert, Felix G.; Ziegelmayer, Sebastian; Luitjens, Johanna; Gassert, Florian T.; Tollens, Fabian; Rink, Johann; Makowski, Marcus R.; Ruebenthaler, Johannes; Froelich, Matthias F. (European Radiology, 2022)
Objective: Pancreatic cancer is portrayed to become the second leading cause of cancer-related death within the next years. Potentially complicating surgical resection emphasizes the importance of an accurate TNM classification. In particular, the failure to detect features for non-resectability has profound consequences on patient outcomes and economic costs due to incorrect indication for resection. In the detection of liver metastases, contrast-enhanced MRI showed high sensitivity and specificity; however, the cost-effectiveness compared to the standard of care imaging remains unclear. The aim of this study was to analyze whether additional MRI of the liver is a cost-effective approach compared to routinely acquired contrast-enhanced computed tomography (CE-CT) in the initial staging of pancreatic cancer. Methods: A decision model based on Markov simulation was developed to estimate the quality-adjusted life-years (QALYs) and lifetime costs of the diagnostic modalities. Model input parameters were assessed based on evidence from recent literature. The willingness-to-pay (WTP) was set to 100,000/QALY. To evaluate model uncertainty, deterministic and probabilistic sensitivity analyses were performed. Results: In the base-case analysis, the model yielded a total cost of 185,597 and an effectiveness of 2.347 QALYs for CE-MR/CT and 187,601 and 2.337 QALYs for CE-CT respectively. With a net monetary benefit (NMB) of 49,133, CE-MR/CT is shown to be dominant over CE-CT with a NMB of 46,117. Deterministic and probabilistic survival analysis showed model robustness for varying input parameters. Conclusion: Based on our results, combined CE-MR/CT can be regarded as a cost-effective imaging strategy for the staging of pancreatic cancer. Key Points: • Additional MRI of the liver for initial staging of pancreatic cancer results in lower total costs and higher effectiveness. • The economic model showed high robustness for varying input parameters.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cancer staging; Cost-effectiveness; Magnetic resonance imaging; Multidetector computed tomography; Pancreatic neoplasms